Direct Synthesis of Graphene Dendrites on SiO2/Si Substrates by Chemical Vapor Deposition - Li, Yingxian; Li, Zhenhua; Li, Qingbo; Tian, Meng; Li, Chunhui; Sun, Li; Wang, Jihua; Zhao, Xian; Xu, Shicai; Yu, Fapeng (Nanoscale research letters, 2020)
The long-standing interest in graphene has recently brought graphene-derived materials including graphene hydrogel, graphene fiber and graphene paper into sharp focus. These graphene-derived materials show outstanding properties in mechanics and physics. In this paper, for the first time, we demonstrate the novel synthesis of graphene dendrites on SiO 2 /Si substrates by chemical vapor deposition. The tree-like graphene dendrites with well-controlled morphology can be directly grown on both the Si and the SiO 2 surfaces of the substrates by using methane and hydrogen as precursors. The graphene dendrites on SiO 2 /Si substrates can be directly used in the fabrication of the electronic device. The conductivity and the Hall mobility of graphene dendrites are ~ 286 Scm −1 and ~ 574 cm 2 (Vs) −1 , respectively. Young’s modulus of graphene dendrites is up to 2.26 GPa. The developed method avoids the need for a metal substrate and is scalable and compatible with the existing semiconductor technology, making graphene dendrites be very promising in nanoelectronic applications.